2023
DOI: 10.3390/educsci13060590
|View full text |Cite
|
Sign up to set email alerts
|

Developing Critical Thinking in Technical and Vocational Education and Training

Abstract: Critical thinking has been difficult to develop in technical and vocational education and training, where acquiring practical skills is often the priority. This study looks at whether tried-and-tested methods for developing critical thinking in higher education are also effective in this educational context. To test this, an intervention was carried out as part of a compulsory, semester-long “Basic Communication Skills” class for 149 first year engineering students. This involved linking the expected learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
0
4
0
5
Order By: Relevance
“…Grammar school students (general secondary education) appeared to have higher scores in MHLS and lower scores in SSOSH. In vocational education, the focus is often on acquiring practical skills, and metacognitive competencies, critical thinking, or other literacies tend to be neglected ( 24 , 25 ). One possible interpretation is that vocational school students may also be more prone to bias and stereotyping in the topic of mental health; however, it needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grammar school students (general secondary education) appeared to have higher scores in MHLS and lower scores in SSOSH. In vocational education, the focus is often on acquiring practical skills, and metacognitive competencies, critical thinking, or other literacies tend to be neglected ( 24 , 25 ). One possible interpretation is that vocational school students may also be more prone to bias and stereotyping in the topic of mental health; however, it needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, positive mental health literacy and education-based programs are likely to be effective in improving MHL among adolescents ( 22 , 23 ). General secondary schools offer more academic subjects, and vocational schools focus on practical skills, this often makes it difficult to develop metacognitive competence, critical thinking, and other literacies in vocational training ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The validity and practicality of the discovery learning e-module on environmental change, suggests that the model itself is effective, but further research is needed to understand its impact on critical thinking skills. The potential of the discovery learning model to improve higher-order thinking skills and metacognitive awareness suggests that it may be a valuable tool for improving critical thinking in the context of environmental change (Ayuningsih & Muna, 2023;López et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Pedagogical strategies for supporting the development of critical thinking skills in chemistry have included: solving real-world problems; inquiry-based practicals; games; writing exercises; scaffolded peer feedback; guided critique; and pre- and postlearning activity quizzes . Similarly, methods to develop chemical literacy often aim to link apparently abstract and theoretical chemistry concepts to their applications in learners’ lives: context-based approaches, storytelling, discussing socio-scientific issues, problem-based learning, and inquiry-based learning have all received attention in the literature. , Some researchers have suggested that using the chemistry literature could be an approach to developing learners’ chemistry literacy, but this is much more common in higher-level courses compared to introductory teaching. , This leaves people who do not want to participate in high-level chemistry education unsupported in developing their chemical literacy and critical thinking skills in chemistry, disadvantaging many learners.…”
Section: Evidence-based Methods For Challenging Chemophobiamentioning
confidence: 99%